"As those who are taught" : the interpretation of Isaiah from the LXX to the SBL - McGinnis, Claire Mathews; Tull, Patricia K. (Symposium series (Society of Biblical Literature), 2006)
This volume offers a survey of the history of Isaiah's reception over the course of two millennia, from the Septuagint and early versions, continuing through the centuries in Jewish and Christian exegesis, and concluding with the late twentieth century. Each chapter includes an introductory survey of Isaiah's interpretation within a particular historical context and then pursues a particular facet of Isaiah's reception by one of Isaiah's many readers in that time period. --From publisher's description.